2016
DOI: 10.1098/rsta.2015.0379
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the quantitative features of surface-assisted laser desorption/ionization mass spectrometric analysis

Abstract: Surface-assisted laser desorption/ionization (SALDI) coupled with mass spectrometry (MS) is frequently used to analyse small organics owing to its clean background. Inorganic materials can be used as energy absorbers and the transfer medium to facilitate the desorption/ionization of analytes; thus, they are used as SALDI-assisting materials. Many studies have demonstrated the usefulness of SALDI-MS in quantitative analysis of small organics. However, some characteristics occurring in SALDI-MS require certain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This is not surprising as coffee ring phenomenon was previously observed in SALDI-MS especially upon using dried droplet method. 42,43 Despite the inhomogeneous distribution been observed after the deposition of the analyte-substrate mixture, a reproducible qualitative and quantitative data with satisfactory relative standard deviation (RSD) were obtained.…”
Section: Oral Fluid Sample Collection and Analysis Using Saldi-msmentioning
confidence: 99%
“…This is not surprising as coffee ring phenomenon was previously observed in SALDI-MS especially upon using dried droplet method. 42,43 Despite the inhomogeneous distribution been observed after the deposition of the analyte-substrate mixture, a reproducible qualitative and quantitative data with satisfactory relative standard deviation (RSD) were obtained.…”
Section: Oral Fluid Sample Collection and Analysis Using Saldi-msmentioning
confidence: 99%
“…The main issue is related to the presence of background interfering species, generated by the ionization of the matrix itself, which are accounted for the suppression of analytes signals in the low mass region of the spectrum. Furthermore, the co-crystallization process, i.e., the inclusion of analyte molecules in the matrix crystals occurring by solvent evaporation at room temperature, causes inhomogeneity of the resulted crystals, the presence of hot spots, and the unwanted coffee-ring effect [1]. The severity of these effects is matrix-dependent and interferes with the possibility of obtaining accurate quantitative results and good reproducibility by MALDI-MS analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In some previous studies, it is reported that the coffee ring effect can be suppressed by fabricating wells on the sample plate through oxygen plasma treatment or additional copper tape. 36,37 In this study, a TiO 2 nanotube array with hydrophilic dot patterns surrounded by hydrophobic areas (HB/HL-patterned TiO 2 NTA) is presented to both distribute analytes uniformly to concentrate them within a sample spot. A vertically aligned one-dimensional (1D) TiO 2 NTA can act as a liquid vessel rather than other nanostructures such as nanoparticles and randomly oriented nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made to suppress the coffee ring effect through sample preparation methods, such as controlling the surface tension, viscosity, pH, and temperature of the sample. However, these approaches usually require specific additional reagents depending on the samples, which make interference mass peaks from chemical additives in LDI-MS. In some previous studies, it is reported that the coffee ring effect can be suppressed by fabricating wells on the sample plate through oxygen plasma treatment or additional copper tape. , …”
Section: Introductionmentioning
confidence: 99%